Diving sports auxiliary training video analysis research - Liu, Z. W. (Information Technology Journal, 2014)
In this study, a video analysis system is developed for diving sports according to the characteristics of the diving sports. This system is mainly used in assisting coach to instruct athletes more effectively and it can help the judgers give the correct judgments. The video analysis, 3D motion simulation, edit interface and the database management are researched. The background and meaning of developing is stated in this system and then the relation and the data flow are analyzed among the main modules. Tracking model and virtual humanmotion modeling are built, the key techniques and innovations are addressed in detail. In practice, this system can not only improve the efficiency of training, reduce the repeated training and the probability of false judgments but also there is the high efficiency in the system and it is easy to be operated.